Risk factors and clinical features in young patients with myocardial infarction: A cross-sectional study - Shivaprasad KR,; Anil Kumar, (Asian Journal of Medical Sciences, 2022)
Background: Changes in lifestyle with increased sedentary lifestyle are associated with its consequences such as obesity, metabolic syndrome, hypertension, diabetes, and eventually myocardial infarction (MI). Coronary artery diseases (CADs) although have been commonly seen in elderly individuals it’s now being increasingly recognized in a relatively younger age group (<45 years). The present study was aimed at analyzing risk factors and clinical presentation of MI in young (<45 years). Aims and Objectives: The aims of this study were to study risk factors and clinical profile of young patients with MI. Materials and Methods: This was a hospital-based prospective cohort study, in which 60 young patients (age <45 years) of age were included on the basis of a predefined inclusion and exclusion criteria. A thorough history was obtained and detailed general and cardiovascular examination was done. Electrocardiogram, basic hematological profile, and 2 D echo were done in all cases. Clinical profile, site of infarction, and severity of systolic dysfunction were studied. P<0.05 was taken as statistically significant. Results: A total of 60 patients were studied. Out of these 60 cases, there were 48 (80%) males and 12 (20%) females with a M: F ratio being 1:0.25. Although the mean age of female patients (40.25±3.44 years) was more than male patients (38.62±4.43 years), the difference was not found to be statistically significant (P>0.05). Obesity, family history of CADs, smoking, dyslipidemia, hypertension, and diabetes were common risk factors in studied cases. Majority of the patients (81.67%) presented with typical chest pain radiating to left arm. The atypical clinical features were seen in 11 (18.33%) patients. In m ost of the patients (63.33%) there was anterior wall infarction. Inferior wall infarction and anteroseptal MI were seen in 12 (20%) and 10 (16.67%) patients, respectively. Conclusion: MI in young patients is increasing. Majority of the risk factors associated with MI in young patients are modifiable risk factors. A high index of suspicion is necessary in diagnosing these patients in time particularly in cases, where there is atypical presentation.